The Influence of Product Quality, Price, Brand Image and Service on Purchase Decisions for Dry Type Ready Mix Concrete: Case Study at PT. XYZ East Java - Megantara, Bayu; Melinda, Tina (Universitas Ciputra Surabaya, 2022)
Infrastructure development is one of the government's priorities in order to accelerate economic growth. Concrete is one of the main materials needed. Not all projects will require and can be delivered ready mixed concrete by using the conventional method, therefore a dry-type ready-to-use concrete (instant concrete) is needed. This study aims to determine the effect of Product Quality, Price, Brand Image and Service on Purchasing Decisions of instant concrete products at PT. XYZ East Java. This is a quantitative research with descriptive type. The data used are primary data obtained through questionnaires and thenprocessed using the SPSS program. The total sample of the study was 34 respondents who were selected using a non propability sampling technique with purposive sampling type. Data analysis used multiple linear regression. The results showed that Product and Service Quality had a significant effect on Purchasing Decisions, while Price and Brand Image had no effect on Purchasing Decisions.